Cardiometabolic markers and serum amh levels in PCOS: can AMH serve as a surrogate cardiometabolic markeR? - Mohammad Ashraf Ganie; Neena Malhotra; Puthiyaveetil Khadar Jabbar; Sarita Aggarwal; Roya Rozati; Rakesh Sahay; Subhankar Chowdhary; Saloni Kamboj; Imtiyaz Ahmad Wani; Taruna Arora; Prasanta Kumar Bhattacharya; Khalid ul Islam Rather (BMC Women's Health)
Abstract Objective To study the cardiometabolic markers in women in with polycystic ovary syndrome (PCOS) across all phenotypes and its correlation with serum anti-mullerian hormone (AMH) levels. Methodology In cross-sectional community-based study aimed to determine the prevalence of PCOS among women aged 19–39 years over 5 years (2018–2022), 10,109 women were found to be eligible from 14,061 approached through a pre validated questionnaire. Out of this cohort, 201 women were diagnosed prior, and from the 2314 probable cases on detailed clinical, ultrasound and hormonal evaluation as per Rotterdam criteria, 860 were true cases. Healthy women from the same community matched for age and BMI, were taken as controls (1174). Both PCOS and healthy controls were assessed for cardio-metabolic indices, including anthropometry (BMI, Waist Circumference (WC), Waist to Hip Ratio (WHR), biochemistry (OGTT with 75 g glucose, lipid profile, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), visceral adiposity index [VAI], lipid accumulation product [LAP]) and fasting and post prandial insulin. Other hormone assays and AMH levels were also assessed in PCOS and controls. Correlation between serum AMH and cardiometabolic indices was calculated for cases using Pearson’s method. Data was analysed using STATA version 18. Main outcome measure(s) Cardio-metabolic profile including obesity/overweight, hypertension, insulin resistance, dyslipidemia among PCOS women and their different phenotypes, comparison with controls and correlation with serum AMH levels in cases. Result(s) In the baseline characteristics, PCOS group had higher systolic and diastolic blood pressure, fasting blood sugar, 2 h oral glucose tolerance test (OGTT), fasting, 30 min and two hours post OGTT insulin levels than control group. In lipid profile, PCOS group had lower High Density Lipoprotein-Cholestrol (HDL-C) and higher low Density Lipoprotein-Cholestrol (LDL-C) levels. HOMA-IR, VAI, LAP were significantly higher in PCOS group. When AMH was correlated with various cardio-metabolic indices in women with PCOS, significant positive correlation was found with BMI, waist circumference, triglycerides and very low Density Lipoprotein cholestrol (VLDL-C) VLDL levels. While correlating AMH with cardio-metabolic indices in different phenotypes, PCOS phenotype A, C, and D suggested a significant positive correlation with BMI, waist circumference, post -prandial blood sugar at 30 min and VLDL-C, while phenotype B correlated only with BMI and VLDL levels. Conclusion(s) A positive correlation could be seen between serum AMH and anthropometric and lipid profile parameters in Indian PCOS women. No such correlation can be established between other insulin resistance markers.